Comparative Study of Religious Liberty in America and Indonesia - Mude, Muhammad Saleh; E. Lovett, Dorothy (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. This article attempts to briefly look at the similarities and differences in the initial conditions for the formation of the two countries: the United States of America and Indonesia, especially in the dynamics of the relations between statesmen and religious leaders, including political relations with religious issues at the beginning of independence until the present. In fact, since 1776, the United States government has chosen a secular-democratic form of state that guarantees freedom of various kinds, and may not protect a particular religion. On the other hand, in Indonesia, although since 1945, the government of the Republic of Indonesia has guaranteed freedom of religion for everyone, in reality, discrimination and persecution of the majority against minorities still often occurs in the name of defending a particular religion.Keywords: The United States of America, Indonesia, Issues of Religious Liberty. Abstrak. Artikel ini mencoba menjelaskan secara singkat kondisi awal tentang persamaan dan perbedaan negara Amerika Serikat dengan Indonesia. Persamaan dan perbedaan yang dimaksud relevansinya pembentukan kedua tersebut, khususnya dalam dinamika hubungan antar negarawan dan tokoh agama, termasuk hubungan politik dengan masalah agama pada awal kemerdekaan hingga saat ini. Padahal, sejak 1776, pemerintah Amerika Serikat telah memilih bentuk negara demokrasi sekuler yang menjamin kebebasan dalam berbagai jenis, dan tidak boleh melindungi agama tertentu. Di sisi lain, di Indonesia, meskipun sejak tahun 1945 Pemerintah Republik Indonesia telah menjamin kebebasan beragama bagi setiap orang, pada kenyataannya diskriminasi dan persekusi terhadap kelompok mayoritas terhadap minoritas masih sering terjadi atas nama membela agama tertentu.Kata Kunci: Amerika Serikat, Indonesia, Isu Kebebasan Beragama.